New records of the water mite genus Koenikea Wolcott, 1900 (Acari: Unionicolidae) from northern and eastern Australia, with the description of six new species - Smit, Harry; Pešić, Vladimir (Zootaxa, 2026)
New records are given of the genus Koenikea from northern and eastern Australia. The following six new species are described: Koenikea yorkensis sp. nov., K. brachypalpis sp. nov., K. interstitialis sp. nov., K. inconspicua sp. nov., K. caniaensis sp. nov. and K. tuberculata sp. nov. The male of Koenikea piota Cook, 1986 is described for the first time. A key is provided for all Australian Koenikea species.